GÖYNÜK VE MUDURNU'DAN YENİ YAZITLAR IV - (:unkn) unknown (My University, 2016)
Makalede Nikaia ve Modrena egemenlik alanında2012-2014 yıllarında bulunan 7 yeni yazıt ile 1 gözdengeçirilen yazıt tanıtılmaktadır. Nikaia ve Modrena antikkentinin teritoryumundan ele geçen tüm yazıtlar Romaİmparatorluk Dönemi'ne tarihlendirilmektedir. Bu yayımlanmamış yazıtlar farklı konudaki birçok bilgininyanında bölgenin kültürel zenginliğini gösteren çok sayıda anthroponymos (şahıs ismi) içermektedir. 1 no'luyazıt onur yazıtıdır. Bu yazıt, Nikaia egemenlik alanında bulunan Ospraimenos/Spraimenos adında yeni birköyün bilgisini vermektedir; 2 no'lu yazıt "Köy Ahalisi"nin İmparator Traianus'a adağıdır. 3-7 no'lu yazıtlarise mezar yazıtıdır.

This article presents 7 new funerary inscriptions found within the territory of Nicaea and Modrena, during the course of survey work undertaken between 2012-2014. All of these inscriptions came from this area, which in the Roman Imperial Period formed a part of the eastern territory of Nicaea and Modrena. These new texts include numerous personal names. All of them underline the cultural richness of these regions in the Roman Imperial Period. These inscriptions provide a range of different information: No. 1 is an honorary inscription giving information of a new kome with the name Ospraimenos/Spraimenos lying within the territory of Nicaea; No. 2 is a votive offering of Kometai to emperor Traian. Nos. 3-7 are funerary inscriptions.
NEW INSCRIPTIONS FROM GÖYNÜK AND MUDURNU IV
Keywords: Arkeoloji